2010
DOI: 10.1007/s10753-010-9255-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Pulmonary Inflammatory and Antioxidant Responses to Intranasal Live and Heat-Killed Streptococcus pneumoniae in Mice

Abstract: Inflammatory and antioxidant responses, in male C57Bl6J mice, to single intranasal inoculations with live or heat-killed Streptococcus pneumoniae were studied in order to tease out differences in responses. Heat-killed bacteria elicited weak lung neutrophil infiltration and raised concentrations (peak 6-8 h), in serum or lung tissue, of CXCL1 and 2, tumor necrosis factor alpha (TNFα), interleukin-6 (IL-6), and granulocyte-macrophage-colony stimulating factor, with later increases in CCL2 and IL-1β. Live bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Neutrophils can infiltrate into lung at an early stage of lung Spn infection [40,41]. In this study, we found that lung bacterial clearance correlated with higher level of phagocytosis by neutrophils at an early stage in pathogenesis after a potential lethal challenge of Spn by the physiologically relevant intranasal route.…”
Section: Discussionsupporting
confidence: 50%
“…Neutrophils can infiltrate into lung at an early stage of lung Spn infection [40,41]. In this study, we found that lung bacterial clearance correlated with higher level of phagocytosis by neutrophils at an early stage in pathogenesis after a potential lethal challenge of Spn by the physiologically relevant intranasal route.…”
Section: Discussionsupporting
confidence: 50%
“…Significant differences for the entire doseresponse curves between saline-sensitized (Saline) and OVA-sensitized (OVA) controls are shown as ## p , 0.01 and between OVA-sensitized and component-treated OVA-sensitized mice as *p , 0.05 and ** p , 0.01. upon treatment with pneumolysoid or ethanol-killed S. pneumoniae, others have detected such responses. Pneumolysoid B (PdB, otherwise known as F433), which is the same as the Ply used in our study, has residual cytotoxic activity and induces CD4 T cell proliferation and the release of low levels of IFN-g and TNF-a (27) Others have detected cytokine release from murine macrophages stimulated with ethanol-killed S. pneumoniae (28), and heat-killed S. pneumoniae elicited weak neutrophilic airway inflammation and cytokine responses mainly from macrophages (29). These studies indicate that pneumolysin derivatives that completely lack cytotoxic and proinflammatory activities should be used in human studies.…”
Section: Discussionmentioning
confidence: 84%
“…It was observed a small and transient peak of GM-CSF in lung of immunocompetent mice after pneumococcal infection which occurred during the early phase of neutrophil infiltration [29]. Although several cytokines can modulate neutrophil production, G-CSF and GM-CSF are the primary regulators of steady-state and emergency granulopoiesis.…”
Section: Discussionmentioning
confidence: 99%